Origin of Resonant Character in the Electron Impact Two‐Body Neutral‐Fragmentation of Methane. Issue 14 (30th May 2022) - Sajeev, Y.; Davis, Daly; Kundu, Sramana; Prabhudesai, Vaibhav S.; Krishnakumar, E.
Abstract: The observation of peaks in the threshold region of two‐body neutral fragmentation of methane molecule, i. e., CH4 → CH3 +H, by low energy electron (LEE) impact has been an enigma. The prevailing explanation that this resonant behavior is due to excitation energy transfer is unsatisfactory since this process is not expected to show peaks in the cross‐sections unless there is the involvement of electron‐molecule resonances. Our first‐principles calculations now reveal that the observed peaks could be explained as due to the formation of negative ion resonances, which dominantly dissociate into two neutral fragments and a free‐electron. This case of methane is a pointer to the possibility that such reactions contribute significantly to neutral radical production from molecules by LEE impact in comparison to dissociative electron attachment, and in general could play a significant role in electron‐based chemical control. Abstract : The origin of resonant character in the low energy electron impact two‐body neutral fragmentation of methane yielding CH3 radical and a hydrogen atom is reported. This molecular fragmentation by the resonant capture, yielding only neutral fragments, are a manifestation of the autodetachment phenomena during the course of fragmentation reaction.